Mixed teaching of design patterns based on MOOC. Issue 1 (July 2021) - Chen, Wenping; Meng, Fanqing; Jiang, Zhenfeng
Abstract: In order to improve teaching effect of the "Java Design Patterns" course, the teaching process uses cases as the main line through the pattern concept, pattern structure diagram, pattern realization, application scenarios and the advantages and disadvantages of the pattern. This teaching method combines the orientation of application-oriented undergraduate, the characteristics of students' knowledge structure and course's abstract nature. In addition, this method combines traditional classrooms and MOOC platforms, and has achieved good results in actual teaching.